New Worm Robot Structure using the Shape-Memory Alloy - Abdolreza Esmaeli (Majlesi Journal of Electrical Engineering)
This paper presents new designing for robot that moves like worm and the structure of this robot is made by the Shape-Memory Alloy (SMA). The smart alloys and the alloys in special kinds of artificial muscles apply motor action to the heat or coldness in the construction of artificial muscles. This robot is controlled by the operator and computer. Imaging, position of detection, smart guidance and environmental factorsâ estimation such as height and impact are other abilities for this robot.